Peran Partisipasi Masyarakat Dalam Penyusunan Perda Tentang Perlindungan Buruh Migran Di Kabupaten Blitar - komarudin, mohammad; Shofwan, Arif Muzayin; Anwar, Moch. Syaifudin (Fakta: Forum Aktual Ahwal Al-Syakhsiyah, 2023)
One of the reform eras was marked by the implementation of democracy in all life in society, nation, and state. In a democracy, the role of community participation in the preparation of regional regulations is very urgent. Therefore, this study examines the role of community participation in drafting a regional regulation on the protection of migrant workers in the Blitar Regency. This qualitative descriptive research uses a sociological juridical approach in conducting its research. The data collection technique used in-depth interviews, documentation, and the participation of researchers in the research area. While the data analysis technique uses content analysis by sorting out the data according to the problem being studied. This study resulted in the following conclusions. First, the role of community participation in the preparation of regional regulations regarding the protection of migrant workers in Blitar Regency is based on Law Number 28 of 1999 Article 9 paragraph 1. migrant workers, including community forums and special committees. Third, the implementation of community aspirations in Blitar Regency is carried out with the following three things, among others: socialization through print and electronic media, stakeholders, and related government.